Effect of Intranodally Administered Dendritic Cell-Based HIV Vaccine in Combination With Pegylated Interferon α-2a on Viral Control Following ART Discontinuation: A Phase 2A Randomized Clinical Trial - Leal, Lorna; Couto, Elvira; Sánchez-Palomino, Sonsoles; Climent, Núria; Fernández, Irene; Miralles, Laia; Romero, Yolanda; González, Tania; Maleno, Maria José; Paño, Blanca; Pich, Judit; Nicolau, Carlos; et al. (Frontiers in Immunology, 2021)
Introduction Functional cure has been proposed as an alternative to lifelong antiretroviral therapy and therapeutic vaccines represent one of the most promising approaches. Materials and Methods We conducted a double-blind randomized placebo-controlled clinical trial to evaluate the safety, immunogenicity, and effect on viral dynamics of a therapeutic vaccine produced with monocyte-derived dendritic cells (MD-DC) loaded with a high dose of heat-inactivated autologous (HIA) HIV-1 in combination with pegylated interferon alpha 2a (IFNα-2a) in people with chronic HIV-1. Results Twenty-nine male individuals on successful ART and with CD4+ ≥450 cells/mm3 were randomized 1:1:1:1 to receive three ultrasound-guided inguinal intranodal immunizations, one every 2 weeks: (1) vaccine ~107 MD-DC pulsed with HIA-HIV-1 (1010 HIV RNA copies) (n = 8); (2) vaccine plus three doses of 180 mcg IFNα-2a at weeks 4–6 (n = 6); (3) placebo = saline (n = 7); and (4) placebo plus three doses of 180 mcg IFNα-2a (n = 8). Thereafter, treatment was interrupted (ATI). Vaccines, IFNα-2a, and the administration procedures were safe and well tolerated. All patients’ viral load rebounded during the 12-week ATI period. According to groups, changes in viral set-point between pre-ART and during ATI were not significant. When comparing all groups, there was a tendency in changes in viral set-point between the vaccine group vs. vaccine + IFNα-2a group (>0.5log10p = 0.05). HIV-1-specific T-cell responses (IFN-ƴ Elispot) were higher at baseline in placebo than in the vaccine group (2,259 ± 535 vs. 900 ± 200 SFC/106 PBMC, p = 0.028). A significant difference in the change of specific T-cell responses was only observed at week 4 between vaccine and placebo groups (694 ± 327 vs. 1,718 ± 282 SFC/106 PBMC, p = 0.04). No effect on T-cell responses or changes in viral reservoir were observed after INFα-2a administration. Discussion Results from this study show that intranodally administered DC therapeutic vaccine in combination with IFNα-2a was safe and well-tolerated but had a minimal impact on viral dynamics in HIV-1 chronic infected participants. Clinical Trial Registration (www.ClinicalTrials.gov), identifier NCT02767193